Cardiac Rehabilitation in Patient with Inferior STEMI, CAD 3VD Post Stent to RCA, DM Type II, Dyslipidemia, and Obesity Grade I - Andi Dala Intan; Tresia Fransiska U.T (Indonesian Journal of Physical Medicine & Rehabilitation, 2015)
Objective: to assess the benefit of Cardiac Rehabilitation (CR) in patient with Inferior STEMI,CAD 3VD Post Stent to RCA, DM Type II, Dyslipidemia, and Obesity Grade IMethods: A retired 59 years old man with presenting diagnosis of STEMI Inferior, CAD 3VD PostStent to RCA, DM Type II, Dyslipidemia, and Obesity Grade I. His medical rehabilitation problemswere myocardial ischemia post revascularization, immobilization, low endurance cardiorespiration,mild dependency of ADL, resolved chest pain and discomfort, and obesity grade I. His rehabilitationdiagnosis (ICF) were B4 of body function and S4 of body structures in cardiovascular, immunological,and respiratory system functions; and D2 of activities and participation in general tasks and demands.His non-pharmacologic therapies of phase I CR program plans included patient education; chestphysical therapy, such as deep breathing exercise, chest expansion exercise; mobility by sittingon a chair and walking around the room for about 5 – 10 minutes in duration, 2 – 3 times/ dayunder supervision; physical Activities about 2-3 Mets, and meet independent ADL. Five days afteradmission, patient underwent 2.5-3 Mets physical activities, starting from getting in and out of thebed with partially independent ADL. Pre-discharge examinations performed were 6 Minute WalkingTest (6MWT). Patients were then assessed on the second week post-discharge for walking distance,VO2max, vital signs, O2 Saturation, Modified Borg Scale before and after tests.Results: On the 5th day of hospitalization when meet the 2.5-3 Mets physical activities, patient wascapable of walking for 100 meters with stabile vital sign (Before: BP 130/70mmHg, HR 70x/m,RR 18x/m, and SpO2 98%; After: BP 131/65mmhg, HR 75x/m, RR 18x/m, and SpO2 98%) andno significant symptoms presented. Pre-discharge 6MWT showed EF 62% without significantsymptoms, maximum distance of 220 meters and VO2 max associated with 3 Mets. Pre-test resultsshowed BP 125/73 mmHg, HR 61 x/m, RR 18 x/m, and SpO2 98%, and Modified Borg Scale 9-0-0. Post-test results included BP 142/76 mmHg, HR 71 x/m, RR 22 x/m, SpO2 98%, Modified BorgScale 11-0.5-0. On the second week post-discharge, the 6MWT was re-performed and showedmaximum distance of 333 meters and VO2 max was associated with 4 Mets. He presented nosignificant symptoms with stabile vital signs (Pre-test results: BP 120/80 mmHg, HR 87x/m, RR 18x/m, SpO2 97-98%, and Modified Borg Scale 7-0-0; Post-test results: BP 142/76 mmHg, HR 107 x/m, RR 20 x/m, SpO2 96-98%, and Modified Borg Scale 9-0-0).Conclusion: CR is essential in comprehensive care of cardiovascular disease patients considering it’s effectivity and efficiency. CR should be monitored and carried out by highly trained health professional along with the active participation of patients and their families. CR will provide satisfying outcome if it is carried out and monitored in a good way.Keywords: Cardiac Rehabilitation, Coronary Artery Disease, Physical Therapy, Exercise, 6MWT